Current status, challenges, and integration pathways of biomarker classification systems in graft-versus-host disease: a preliminary exploration - Yu, Xinxin; Huang, Shuai; Li, Xiaoxia; Zhao, Yizhuo; Jin, Xiaohan; Fan, Meiqi; Zhang, Yuanfeng; Ma, Lusheng (Frontiers in Medicine, 2025)
BackgroundGraft-versus-host disease (GVHD) is a life-threatening complication of allogeneic hematopoietic stem cell transplantation that impairs clinical outcomes. Existing classification systems for GVHD biomarkers remain fragmented, which limits cross-study data integration and clinical translation, creating an urgent need for a systematic classification framework.Materials and methodsIn this review, a predefined search strategy was used to systematically evaluate the classification systems of GVHD biomarkers. For the search, a systematic literature retrieval was conducted in the PubMed and Web of Science databases, covering the time range from 2012 to 2025, with keywords including “GVHD,” “biomarkers,” and “classification and summarization.” The inclusion criteria for studies were as follows, focusing on the classification or clinical application of GVHD biomarkers: peer-reviewed original articles, reviews, or multicenter trials, and human subjects or well-validated mouse models. After screening, a total of 139 articles were included in this review.ConclusionThis review integrates GVHD biomarkers into a three-dimensional system, including pathophysiological mechanisms, clinical application scenarios, and molecular characteristics. It identifies key challenges in biomarker research and application, and proposes feasible integration pathways. This work provides a foundational framework for precision medicine in GVHD management.